Sensitivitas dan Spesifisitas Pemeriksaan Antibodi Human Immunodeficiency Virus (HIV) dengan Perbedaan Metode Imunokromatografi Rapid Test terhadap ECLIA (Electro Chemiluminescence Immuno Assay) - Aini, Resmi; Padmarini, Adira; Sulistyo, Andhy (Jaringan Laboratorium Medis, 2025)
The requirement for HIV reagents using the Immunochromatographic Rapid Test method must comply with the WHO prequalification standards and evaluation by the National Evaluator Agency to ensure their quality and safety; therefore, their sensitivity and specificity were tested against the ECLIA method as the gold standard. To determine the sensitivity and specificity of HIV testing using the Immunochromatographic Rapid Test compared with ECLIA at UDD PMI Yogyakarta City. The study population consisted of all blood donor samples undergoing screening for transfusion-transmissible infections (TTI). Sampling was conducted using the Systematic Random Sampling technique, by determining a random starting point with a Random Number Generator and subsequently selecting samples at fixed intervals until 30 samples were obtained. These samples were then tested using both ECLIA and the Rapid Test. The study design was observational analytic with a cross-sectional approach to evaluate the correlation between Rapid Test results and the ECLIA method as the gold standard, and to calculate sensitivity, specificity, PPV, and NPV accurately. A total of 30 blood donor samples were examined. Based on the ECLIA results, 4 samples were identified as HIV-reactive and 26 samples were non-reactive. The Immunochromatographic Rapid Test detected only 2 of the 4 ECLIA-confirmed reactive cases. The test showed high specificity (100%) but relatively low sensitivity (50%). ECLIA detected 4 (13.3%) reactive and 26 (86.3%) non-reactive samples. The sensitivity of the Immunochromatographic Rapid Test compared to ECLIA was 50%, while the specificity was 100%. These results indicate that the Rapid Test does not meet the requirements stated in the 2018 CPOB guidelines, particularly regarding HIV screening, which requires a specificity of more than 98%.